Family conflict and slow growth. Issue 4 (1st October 1997) - Montgomery, Scott M; Bartley, Mel J; Wilkinson, Richard G
Abstract : AIMS: Having previously observed that slow growth in childhood is associated with subsequent labour market disadvantage, an attempt was made to determine whether family conflict is associated with slow growth to age 7 years, independently of material disadvantage. METHODS: A total of 6574 children born between 3 and 9 March 1958 who were members of the British National Child Development Study were used in these analyses. Slow growth at age 7 years was indicated by short stature defined as the lowest fifth of the height distribution. In multivariate analysis, adjustment was made for fully attained adult height as a measure of genetically predetermined height. RESULTS: A total of 31.1% of children who had experienced family conflict were of short stature compared with 20.2% of those who had not, representing relative odds of 1.79 (95% confidence interval (CI) 1.39 to 2.30). After adjustment for social class, crowding, sex, and predetermined height, the relative odds were slightly reduced to 1.62 (95% CI 1.18 to 2.23). A total of 44.0% of children from the most crowded households were of short stature compared with 16.4% of those from the least crowded. The unadjusted relative odds were 3.99 (95% CI 2.94 to 5.41) and after adjustment for the potential confounding variables they were 3.07 (95% CI 2.08 to 4.51). Low social class was also a risk for short stature at age 7 years, but this was not statistically significant after adjustment for the other confounding factors. CONCLUSIONS: Family conflict during childhood was independently associated with slow growth to age 7 years.